Atypical Clinical and Diagnostic Features in Ménétrier's Disease in a Child - Michael Chung; Jaime Pittenger; Deborah Flomenhoft; Jeffrey Bennett; Eun-Young Lee; Harohalli Shashidhar (Case Reports in Gastrointestinal Medicine, 2011)
Ménétrier's disease is one of the rarest protein-losing gastropathies in childhood. It is characterized clinically by non-specific gastrointestinal symptoms and edema, biochemically by hypoalbuminemia, and pathologically by enlarged gastric folds. In adults, this disease can be devastating with significant morbidity and mortality. In childhood, it is a self-limiting, transient and benign illness. Its treatment is largely supportive with total parenteral nutrition (TPN) while oral intake is encouraged. Acute onset of vomiting in healthy school age children can be initially explained by acute viral gastroenteritis. However, persistent vomiting associated with hematemesis and severe abdominal pain should warrant further work-up. This case report illustrates a self-limiting and rare cause of protein-losing enteropathy called Ménétrier's disease that presented with several variant clinical features not typically described in association with this entity.